(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One of the most important stages of life is adolescence, and since it is so important we shouldfocus our efforts to solve the challenging conditions like mental depression, anxiety and stress. It is notthat simple on an account of the multi-factorial changes that are taking place in that period such asbiological, physiological and psychological. Psychiatric disorders in this period are a major public healthconcern because of their impact on the life in almost every aspect from poor academic performance,substance abuse to the suicide attempts because adolescence is really a stage of changes in body andbehaviour that may affect mental health to such extent that one can end up his or her life. We found thatonly few studies have been done to know the causes of mental depression and anxiety in adolescenceas well as among the science students at school level and specifically on the mental depression amongscience students at Higher Secondary Level in this vying world where every second one has to facecompetition for marks to get what one has desired. This article is based on the major causes of mentaldepression among science students only and will suggest or recommend avoiding such conditions fromwhere the journey of mental depression begins and will affect the academic performance badly.